Heartburn - Ephron, Nora 1941-2012 (Knopf, 1983)
When her husband announces that he is in love with another woman, Rachel, a noted cookbook author and TV personality, returns to New York and her wacky but loving family and friends to sort out her life.
Keywords: Domestic fiction; Food writers -- Fiction; Married people -- Fiction